Carbon stock assessment in areca nut and shade trees of coffee and cardamom plantations - Devakumar, A.S.; Babu, K.R.; Reddy, N.V. Eashwar; Anand, B. (Indian Journal of Agroforestry, 2020)
This study is an attempt to quantify the carbon stocks in areca nut and shade trees of coffee and cardamom plantations. Tree size varied considerably in three plantations. DBH of seven year old areca nut trees was 58 cm, while it varied between 117 to 161 cm in shade trees of coffee and cardamom plantations. Tree density was 1083 tree/ha in areca nut while it was 233 and 260 tree/ha in coffee and cardamom plantations respectively. Above ground biomass was maximum in cardamom plantation, though the tree density was more than four times higher in areca nut plantation. This suggests that tree density and DBH are mutually exclusive. SOC did not differ among the plantations however, litter accumulation varied and it was highest in coffee plantations. This was due to deciduous and perennial nature of both shade and coffee plants. Total carbon stock contributed from above ground biomass, litter and SOC was highest in cardamom with 194.27 Uha and was least in areca nut with 159.48 t/ha, while coffee recorded 170.12 Uha. Highest tree diversity of 61 tree species was recorded in coffee plantation and 21 in cardamom plantation. With coffee plantations occupying highest land area among the three crops and with higher tree diversity, the contribution towards carbon stocking and biodiversity conservation would be considerable among the plantation crops.